Acute phase serum proteins in syngeneic and allogeneic mouse pregnancy. - Waites, G T (1983)
The levels of two murine acute phase proteins, serum amyloid P component (SAP) and haptoglobin, have been measured in the serum of C57BL/10 female mice during syngeneic and allogeneic pregnancy. Both syngeneic and allogeneic pregnancy resulted in alterations in the levels of these proteins as compared to those observed in virgin females. Syngeneic mating resulted in an increase in concentration of both proteins during the final 3 days of pregnancy. During allogeneic pregnancy, SAP levels, after a transient increase on day 4, rose from days 6-8 and, after remaining relatively stable, increased from day 12 to reach maximum levels on day 18 of pregnancy. Levels fell dramatically during the immediate post-partum period. In contrast, although levels of haptoglobin also increased from days 6-8, for the remainder of pregnancy these increased levels remained stable. The implications of these findings are discussed in relation to the mechanisms of regulation of acute phase reactants and the immunological relationship between the mother and fetus.